Strategic HR Practices and Sustainable Competitive Advantage in Manufacturing Firms in Bahrain - Almuslamani, Hashem Ali Issa; Daud, Salina (International Journal of Psychosocial Rehabilitation, 2020)
Recently, strategic human resource (HR) practices have increasingly been recognized as sources of sustainable competitive advantage, and main contributors when it comes to implementing business goals and objectives. Grounded on the theoretical perception of the resource-based view, this article examines the effects of strategic human resource practices on sustainable competitive advantage in large medium, and small-sized manufacturing firms in Bahrain. A cross-sectional survey was applied in this study utilizing a self-administered questionnaire to collect data. The usable questionnaires was 159 and the response rate was 75.4%. The findings indicated that strategic HR practices have significant and positive effects on the sustainable competitive advantage in small, medium and large firms in the manufacturing sector. These findings could help these manufacturing firms to achieve a sustainable competitive advantage by improving and supporting strategic HR practices.